Dragonbreath: Revenge of the Horned Bunnies #6 - Vernon, Ursula (New York : Dial Books, 2012)
Danny Dragonbreath is excited about going to camp with his best friend Wendell and classmate Christiana even though his obnoxious, seven-year-old cousin Spencer is going too, but things change when Spencer finds a real jackalope.
Keywords: Camps -- Juvenile fiction; Cousins -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Dragons -- Juvenile fiction; Iguanas -- Juvenile fiction; Camps -- Fiction; Cousins -- Fiction; Animals, Mythical -- Fiction; Dragons -- Fiction; Iguanas -- Fiction; Humorous Stories